BDNF Actions in the Cardiovascular System: Roles in Development, Adulthood and Response to Injury - Kermani, Pouneh; Hempstead, Barbara (Frontiers in Physiology, 2019)
Abstract The actions of BDNF in regulating neuronal development and modulating synaptic activity have been extensively studied and well established. Equally important roles for this growth factor have been uncovered in the cardiovascular system, through the examination of gene targeted animals to define critical actions in development, to the unexpected roles of BDNF in modulating the response of the heart and vasculature to injury. Here we review the compartmentally distinct realm of cardiac myocytes, vascular smooth muscle cells, endothelial cells, and hematopoietic cells, focusing upon the actions of BDNF to modulate contractility, migration, neoangiogenesis, apoptosis and survival. These studies indicate that BDNF is an important growth factor which directs the response of the cardiovascular system to acute and chronic injury.